IL-2 and IL-10 levels in induced sputum and serum samples of asthmatics - (:unkn) unknown (HOGREFE & HUBER PUBLISHERS, 2004)
Background: There is consisting evidence that asthma is associated with airway inflammation. Originally IL-10 and IL-2 were described as lymphokines produced by T cells in mediating cellular infiltration into the airways and continue to be of interest in evaluating asthma pathogenesis. The aim of this study was to evaluate the serum and sputum levels of IL-2 and IL-10 in asthmatic subjects and healthy controls and to correlate disease activity and other clinical indices with concentrations of IL-2 and IL-10 in serum and sputum samples. Methods: We evaluated cell profiles and IL-2 and IL-10 levels in induced sputum samples and in serum samples of 6 mild, 5 moderate, 7 severe asthmatic patients and 5 healthy controls by using ELISA. Results: The mean IL-2 in sputum samples of asthmatics and controls were 35.3+/-13.2 pg/ml and 35.3+/-8.4 pg/ml, respectively. The mean IL-2 in serum samples of asthmatics and controls were 42.7+/-21.1 pg/ml and 30.3+/-2.4 pg/ml, respectively. Both levels did not result in any statistically significant difference between asthmatics and controls. There was no correlation between serum and sputum IL-2 levels, however sputum IL-2 levels correlated with percentage of sputum lymphocytes (p<0.03, r=0.51). The mean IL-10 levels in sputum samples of asthmatics and controls were 4.4&PLUSMN;3.3 pg/ml and 3.9&PLUSMN;5.9 pg/ml, respectively, the mean IL-10 level in serum of asthmatics and controls were 4.1&PLUSMN;3.8pg/ml and 2.3&PLUSMN;2.5 pg/ml, respectively. We could not find statistically significant difference of serum or sputum IL-10 levels between asthmatics and controls There was only correlation between serum and sputum IL-10 levels in asthmatics (p<0.0008, r=0.73). There was no difference between asthmatic subgroups regarding sputum and serum levels of IL-2 and IL-10. No correlation could be demonstrated between sputum or serum IL-2 and IL-10 levels and clinical severity. Conclusions: We have demonstrated the presence of detectable concentrations of the IL-2 and IL-10 in serums and induced sputum samples of asthmatics. however, they have no predictive value for asthma since their levels are not increased in asthmatic patients over controls. Moreover, IL-2 level positively correlated with lymphocyte percentage in induced sputum. The results suggest that measurement of IL-2 and IL-10 concentrations in serum and sputum will not be of diagnostic use in asthma and a reflection of the severity of asthmatic airway inflammation.
Keywords: IL-2; IL-10; induced sputum; asthma; MESSENGER-RNA EXPRESSION; ALLERGEN INHALATION CHALLENGE; BRONCHOALVEOLAR LAVAGE FLUID; COLONY-STIMULATING FACTOR; T-CELL-CLONES; CYTOKINE PRODUCTION; ATOPIC ASTHMA; PERIPHERAL-BLOOD; AIRWAY INFLAMMATION; BRONCHIAL BIOPSIES